A study of the profile of 4th year high school students of Baguio City National High School with implications on their use of electronic resources - Ganancial, Ana Jean D.; Gonzales, Grace Marie B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2004)
Electronic resources and online resources have greatly affected the information world. The arrival of the information age has challenged libraries and information systems to move toward becoming electronic by including electronic resources in the library collection. At present, the youth are heavily relying on the internet and various electronic resources that are readily available for their research and other information needs. This is because of the accessibility, convenience, and speed of the resources.
The main objective of this research was to study the profile of the fourth year Special Science student of BCNHS with implication on their use of electronic resources. The fourth year Special Science students of BCNHS were chosen to be the population of this particular study. The respondents were chosen because they are at least of similar age, same academic subjects and are aware of the existence and use of electronic resources.
The primary significance of this study is that it could give insights to other schools in their future library planning and the inclusion of electronic resources into the library collection for a more effective and efficient library service. Since the research study only took into account student profile (gender) with implication to their use of electronic resources, it used the survey technique that is wholly descriptive and quantitative. The researcher used a structured questionnaire with close - ended questions in the checklist format to satisfy the needs of this study.
It was discovered that most of the students are already aware of the existence of electronic resources and are already aware of the existence of electronic resources and already using the resources. The study showed that majority of the students access electronic resources in their respective homes or outside the school rather than in the school library and are using these resources for a period of an hour or more 2-3 times a week. Furthermore, the students are using these electronic resources primarily for information and communication purposes.
The recommendation part of this study was devoted to giving suggestions on following measures or steps that can be taken by the school administration or library in promoting the use of electronic resources among the students such as: (1) have a compilation of the websites, search engines and electronic resources that would be useful to the students and (2) setting up an Internet Access Center inside the school premises and inclusion of electronic resources in the library collection with the help of organizations.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Baguio City National High School -- Students; High school students -- Philippines -- Baguio City; Electronic resources -- Use studies. -- Philippines -- Baguio City